Islamic Law Review on Default and Unlawful Acts in Online Lending Practices - Fatihani Baso; Kholifah, Ayu (Wealth: Journal of Islamic Banking and Finance, 2022)
Debt in Islam is a social observance with the concept of helping (ta'awun). The presence of information technology-based lending is an innovation that aims to provide convenience for consumers to access needs in the form of loan funds. However, the presence of these online lending has taken many victims with many debtors receiving loans experiencing greater losses due to default disputes and unlawful acts in online lending practices. Indonesia as a country with the largest Muslim population needs to review this phenomenon from the point of view of Islamic law. The goal is that the society will not only become good citizens, but also become Muslims who are obedient to the provisions of Islamic law. This research is normative legal research which is also called doctrinal legal research. Descriptive analysis will be presented through literature study techniques from secondary data in the form of library materials. The results of the study show that online loans that have a great potential to cause default disputes and unlawful acts are a madharat that must be eliminated. The reason for making it easy to provide benefits to the community must be reviewed, because eliminating harm must take precedence over achieving benefit